Transformasi Model Pembelajaran Pendidikan Agama Islam Berbasis Literasi Digital: Analisis Konseptual - Ash shifa Annur; Nurbayani Nurbayani; Salami Mahmud; Aisyah Aisyah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2025)
This study aims to conceptually analyze the transformation of Islamic Religious Education (PAI) learning models based on digital literacy. A qualitative approach with a library research design was employed to understand, interpret, and synthesize ideas, concepts, and learning models of PAI from theoretical studies and previous research (2018–2024). The data sources included scholarly literature, such as academic books, national and international journal articles, and research reports, which were selected using a qualitative systematic literature review (SLR) approach. Data analysis was conducted through content analysis and qualitative descriptive methods, following the model of Miles, Huberman, and Saldaña, including data reduction, data presentation, and conclusion. The findings indicate that the transformation of PAI learning in the digital era involves: (1) an epistemological shift from a normative-transmissive approach to a constructive-reflective approach, with teachers acting as epistemic facilitators; (2) the integration of digital pedagogy based on critical literacy through the use of TPACK and the SAMR model, enabling students to actively construct meaning and produce digital religious content; and (3) the internalization of spiritual and digital ethical values, emphasizing digital manners, tafakkur (reflection), ijtihād (critical reasoning), and tablīgh (religious dissemination) within the digital learning ecosystem. This transformation supports the development of holistic learners who are intelligent, critical, creative, and virtuous. The study contributes to Islamic education scholarship by highlighting digital literacy as an instrument for cultivating moral character and reinforcing maqāṣid al-tarbiyah values, rather than merely technological skills. Practically, it requires PAI teachers to develop new roles as moral and pedagogical facilitators in digital learning environments.